2018
DOI: 10.1159/000489876
|View full text |Cite
|
Sign up to set email alerts
|

Widely Spread Unilateral Inflammatory Linear Verrucous Epidermal Nevus (ILVEN)

Abstract: Inflammatory linear verrucous epidermal nevus (ILVEN) is an epidermal nevus that clinically and histologically mimics linear psoriasis. The pathogenesis of psoriasis has been widely investigated, with recent studies focusing especially on targeting proinflammatory cytokines such as IL-17A, TNFα, IL-23, and IL-12, while little is known about ILVEN. Since the treatment for ILVEN varies widely from the administration of topical ointment for psoriasis to invasive methods such as carbon dioxide gas laser, the diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 11 publications
0
7
0
4
Order By: Relevance
“…13 Tanita et al reported a case of wide-spread unilateral ILVEN that clinically and histologically mimicked psoriasis vulgaris but was distinguishable by immunohistochemical staining focused on the IL-36γ/IL-17a axis. 21 They showed that while lesional skin of both entities possessed IL-36R cells, the expression of IL-36γ was decreased on the epidermal keratinocytes in ILVEN compared with that in psoriasis lesions. The tendency of both IL-17-producing cells and IL-17R expression was similar in the two groups.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…13 Tanita et al reported a case of wide-spread unilateral ILVEN that clinically and histologically mimicked psoriasis vulgaris but was distinguishable by immunohistochemical staining focused on the IL-36γ/IL-17a axis. 21 They showed that while lesional skin of both entities possessed IL-36R cells, the expression of IL-36γ was decreased on the epidermal keratinocytes in ILVEN compared with that in psoriasis lesions. The tendency of both IL-17-producing cells and IL-17R expression was similar in the two groups.…”
Section: Discussionmentioning
confidence: 98%
“…They showed that while lesional skin of both entities possessed IL‐36R cells, the expression of IL‐36γ was decreased on the epidermal keratinocytes in ILVEN compared with that in psoriasis lesions. The tendency of both IL‐17‐producing cells and IL‐17R expression was similar in the two groups 21 . With similar IL‐17 receptor expression among epidermal keratinocytes of both ILVEN and psoriasis 21 and knowing IL‐17 receptor blockers are an effective treatment in psoriasis vulgaris, 22 it was conceivable that such a biologic agent would be suitable for ILVEN treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Distinction with linear psoriasis can be difficult histologically. Retinoids and local corticosteroids are not very effective, surgical excision is sometimes practiced and CO2 laser finds its place in this indication with satisfactory results [1][2][3].…”
mentioning
confidence: 99%